Enfoque actual de diabetes mellitus tipo 2 en mayores de 45 años de puerto bolívar. - Quezada Rosales, Xavier Andres (2018)
Introduction: Diabetes mellitus, is presented at any age, being the result of an auto-immune process, associated with genetic predisposition, triggered by environmental factors, or presented by decreased production of insulin. The Ministry of Public Health of Ecuador presents diabetes mellitus as a disease which must be controlled through a multidisciplinary approach that should include preventive, educational strategies for both patients or relatives who are Their care, to carry out counseling processes in order to be able to reduce the complications. At present, primary health care plays an important role, in monitoring people with diabetes mellitus as it is presented as a vulnerable and risk group in the population, this research is focused on studying the high rate of Incidence of morbidity and the quality of care provided to patients with type 2 diabetes mellitus, in the external consultation of the Puerto Bolívar Health Center. This research addresses some epidemiological factors, incidence and morbidity in patients with type 2 diabetes mellitus, 07d02 district. Objective: To characterize the patients with type 2 diabetes mellitus in the Puerto Bolívar Health Center as a tool that allows to act on epidemiological elements that help in the prevention avoiding the appearance of complications through the collection of information used in the 07d02 district. Results: The highest incidence of type 2 diabetes mellitus was from 45 years, and in the female sex, the main personal antecedent was the arterial hypertension, the family history of diabetes mellitus was present in a third part of diabetics and Cardiovascular complications predominate. It should be emphasized that in the Puerto Bolívar Health Center all its patients with diabetes mellitus have a monthly control, in order to reduce the risk of complications. Discussion: Hormonal alterations, bad eating habits, inadequate projection to treat from early stages to relatives of diabetic patients lead to mainly cardiovascular complications in these patients and their emergence after The 45 years mainly in women. The presence of hypertension is an aggravating factor in the prognosis of diabetics. It could be shown that most of the patients who are cared for in the Puerto Bolivar Health Center If they are aware of their disease and complications, in which it is possible to realize that the education that all health personnel must carry out, if it is being fulfilled. Conclusions: It was evidencio that diabetic patients type 2 older than 45 years in Puerto Bolivar, was mainly affected the female sex, the morbidity tube 13.4% in males and women 13.89%, the most important complications were cardiovascular. Although in our investigative work was not raised if diabetes negatively affected the quality of life of people, it was clear at the time to socialize with them that emotional involvement was high because the majority of patients who suffer from this Disease are people over 45 years old who could still maintain adequate physical and intellectual activity.